Structure of physical fitness among young female basketball players (trends of changes in 2006-2013) - Karpowicz, K.; Karpowicz, M.; Strzelczyk, R. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to identify trends of changes in the structure and levels of motor effects among young women basketball players in 2006-2013. These changes were examined in the context of comprehensive development of functional, fitness-related, and technical fundamentals with respect to requirements of specific training adopted as typical for targeted sports training stage. The research material was collected in 2006-2013 among young basketball players from the Greater Poland region. The study evaluated 169 girls (mean ± SD: age = 15.5 ± 0.5 years; height = 173.5 ± 5.8 cm; weight = 60.2 ± 7.9 kg). The measurements focused on the structure of motor effects in the athletes studied. For this purpose, the study used the International Physical Fitness Test. The study found that overall physical fitness of young women basketball players has been declining year by year. On the one hand, this might have been caused by the tendency for regression in motor modifications across generations that have been observed among populations. On the other hand, changes in weight-height ratio toward increasing obesity have also been observed. The results may serve as a kind of expertise about the structure of motor development of successive age groups of sports talented young women in light of training objectives at the targeted sports training stage as compared with trends typical for the general population. By describing the results of long-term research, this article offers a way of detecting possible positive or negative tendencies at a relatively early stage.